Targeting Apoptosis Resistance in Rhabdomyosarcoma - Fulda, Simone (Current Cancer Drug Targets, 2008)
Resistance of human cancers to current treatment approaches remains a challenge in oncology. Therefore, there has been much interest in identifying molecular pathways that are responsible for primary or acquired resistance of cancers. Since most anticancer therapies, i.e. chemotherapy or radiotherapy, primarily act by triggering programmed cell death (apoptosis) in cancer cells, defects in apoptosis programs may confer resistance. Evasion of apoptosis in rhabdomyosarcoma may be caused by the dominance of cell survival pathways, for example aberrant activation of the PI3K/Akt/mTOR cascade, or alternatively, by defective expression or function of critical mediators of apoptosis, i.e. components of the TRAIL signaling system. In addition, signaling to apoptosis can be blocked under hypoxia, a characteristic feature of most solid tumors including rhabdomyosarcoma that has been associated with poor treatment response. Thus, molecular targeted therapies that are specifically directed to the defects in apoptosis programs, open novel perspectives to restore apoptosis sensitivity in rhabdomyosarcoma.
Keywords: hypoxia